2005
DOI: 10.1002/chin.200527208
|View full text |Cite
|
Sign up to set email alerts
|

New Triple‐Helix DNA Stabilizing Agents.

Abstract: New Triple-Helix DNA Stabilizing Agents. -All compounds show triple-helix stabilizing activity. Compounds (I) also show strong duplex stabilizing activity with compound (Ic) being the most selective towards duplex DNA. Compounds (II) do not stabilize duplex DNA, they are completely triple-helix selective. -(STREKOWSKI*, L.; HOJJAT, M.; WOLINSKA, E.; PARKER, A. N.; PALIAKOV, E.; GORECKI, T.; TANIOUS, F. A.; WILSON, W. D.; Bioorg. Med. Chem. Lett. 15 (2005) 4,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 1 publication
1
8
0
Order By: Relevance
“…Subsequently, it has been found that 2-arylquinolin-4-amines can intercalate with double-and triple-helical DNA. Importantly, it has been demonstrated that compounds can be designed for selective stabilization of triplex DNA in the presence of duplex DNA [5][6][7][8][9][10][11][12][13]. Additional studies have shown that certain quinolines and acridines are antagonists of immunostimulatory bacterial DNA [14][15][16][17] and, as such, can induce remissions of the rheumatoid arthritis and systemic lupus erythematosus.…”
Section: Introductionmentioning
confidence: 97%
“…Subsequently, it has been found that 2-arylquinolin-4-amines can intercalate with double-and triple-helical DNA. Importantly, it has been demonstrated that compounds can be designed for selective stabilization of triplex DNA in the presence of duplex DNA [5][6][7][8][9][10][11][12][13]. Additional studies have shown that certain quinolines and acridines are antagonists of immunostimulatory bacterial DNA [14][15][16][17] and, as such, can induce remissions of the rheumatoid arthritis and systemic lupus erythematosus.…”
Section: Introductionmentioning
confidence: 97%
“…We wished to examine whether the PET assay approach could be extended to the use of the acridine conjugate 7 with the simplicity of using bromine substitution within the acridine ligand to promote recognition and binding to triplex DNA. Normally, acridine acts as a potent duplex DNA intercalator [8,9] but the presence of bromine atom at position 1 3 C2 has been shown to redirect its specificity for triplex DNA [10].…”
Section: Introductionmentioning
confidence: 99%
“…Given the importance of triplexes in RNA biology, small molecules capable of recognition, binding, and stabilization of the triple-helical RNA structures are attracting growing interest as potential molecular biology tools and therapeutic agents. In contrast to numerous studies on DNA triplexes, 12,13 the interaction of small molecules with RNA triplexes have been far less investigated. Examples of the compounds stabilizing RNA triplexes involve mainly organic compounds, amino-glycosides, and various dyes, such as neomycin, 14 tunable diphenylfuran-based scaffold (furamidine), 15 imidazoles and benzimidazoles, 16 flavonoids, 17 alkaloids and their analogues, 18,19 proflavine and its Pt conjugate, 20 and transitionmetal-based complexes based on Ru(II) polypyridyl complexes.…”
Section: ■ Introductionmentioning
confidence: 99%